Digital Monetization of YouTube Super Chat Feature: An Imam Al-Shatibi Perspective - Rohmat, Muhammad Rohmat Hidayat; Ab Rohman, Siti Fatinnah binti; Azizah, Ninik; Masrokhin, Masrokhin (Fakultas Agama Islam, Universitas Hasyim Asy'ari, 2025)
In its development, the YouTube platform has been utilized by users for promotional purposes or as a source of income, even becoming a primary occupation as content creators or YouTubers. Features like Super Chat allow viewers to pay in order to have their messages prioritized during live broadcasts, thereby creating an economic relationship within the digital public communication space. This study employs a qualitative research method with a literature review approach, using the normative-philosophical framework of Imam al-Shāṭibī. The article evaluates the legitimacy and benefits of digital donation practices based on Islamic legal principles such as mutual consent (attaraḍin), protection of wealth (ḥifẓ al-māl), and considerations of public interest (maṣlaḥah) and harm (mafsadah). The findings indicate that the Super Chat practice can be deemed permissible under Islamic law, provided it is conducted voluntarily, does not violate Islamic values, and supports beneficial objectives such as da'wah (Islamic preaching), education, and wholesome entertainment. This study emphasizes the importance of the maqāṣid al-shariʿah approach in responding to the evolving dynamics of Islamic legal discourse in the digital era.